MODEL PEMBELAJARAN LATIHAN INKUIRI UNTUK MENINGKATKAN PENGUASAAN KONSEP ENERGI RUMAH TANGGA DAN KETERAMPILAN BERPIKIR KREATIF SISWA SMP - Budiman, Indra (Wahana Karya Ilmiah Pendidikan, 2023)
Abstract. Training inquiry learning model in this research is applied for improvement concept achievement and creative thinking skills in Junior High School for subject matter energy. Metodology of this research is Quasi Experimental with pretest-postest-control group design. The population is grade’s XI student of SMPN Purwakarta that there are 9 class. We take random from 9 class, that one class as experimental class and one class as control class. The number of sample is 41 students for experimental class and 41 students for control class. The research’s data are paper and pen test (pretest and postest), quesionaire, observation and interview. The research’s data are done with consider their normality and homogenity. And than mean difference test with Wilcoxon test. The result of study show that there are raising concept achievement and creative thinking skills after training inquiry learning model is apllied better than conventional learning. N-gain of concept achievement is 51% for experimental class and 33% for control class. N-gain for creative thinking skills is 48% for experimental class and 21% for control class. Keywords: Training inquiry learning model, concept achievement, creative thinking skills, subject matter energy